Failure mechanism of lead-free component boards in thermomechanical test based on recrystallization enhanced cracking. (July 2020) - Xu, Hongbo; Liu, Fa; Zhou, Li; Zhao, Hongyun; Li, Mingyu
Abstract: The purpose of this paper is to make a comprehensive understanding of the trends between the lifetime and the thermomechanical test setup parameters, based on the physical failure mechanism of SnAgCu solder interconnections in the component boards. The thermomechanical tests, including thermal cycling and thermal shock, were employed to investigate the failure of the component boards under different loading conditions. The in situ observation during the thermomechanical tests was employed to study the microstructure evolution and the crack propagation of solder interconnections. Electrical failures of the component boards under all setup conditions are mainly caused by the cracks, which propagate along the continuous network of the high-angle grain boundaries produced by the distinguished recrystallization of solder interconnections. The propagation of cracks is highly dependent on the expansion of the recrystallized volume in the solder interconnections. In addition, the expansion of the recrystallization would be influenced by the setup parameters of the thermomechanical test. The paper discusses the relationship among the four factors of the lifetime, the crack growth, the restoration phenomenon and the test setup parameters, in order to explain the complicated trend between the component board lifetime and the setup parameters.